2015
DOI: 10.1002/prp2.192
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‐27b levels are associated with CYP3A activity in vitro and in vivo

Abstract: Previous in vitro studies have shown that microRNA‐27b (miR‐27b) may regulate mRNA levels of CYP3A4, vitamin D receptor (VDR), and Peroxisome proliferator‐activated receptor α (PPAR α) as well as CYP3A4 protein expression and activity. In vitro studies have also shown that vitamin D may affect the expression of CYP3A4. The primary aim of this pilot study was to investigate the association between miR‐27b and CYP3A expression and activity. The secondary aim was to investigate the association between 25‐hydroxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Previous studies have also demonstrated that miR-27b-3p regulates the expression of CYP3A4 15. , 16. , which is the most abundant hepatic and intestinal drug metabolizing enzyme in humans 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also demonstrated that miR-27b-3p regulates the expression of CYP3A4 15. , 16. , which is the most abundant hepatic and intestinal drug metabolizing enzyme in humans 17 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, miR-27b-3p has been shown to negatively regulate the expression of cytochrome P450s (CYPs) 1B1 in human carcinoma cells13., 14.. Previous studies have also demonstrated that miR-27b-3p regulates the expression of CYP3A415., 16., which is the most abundant hepatic and intestinal drug metabolizing enzyme in humans 17 . Changes in CYP3A4 expression and function will undoubtedly lead to a broader variability in drug metabolism as CYP3A4 contributes to the biotransformation of more than 50% of the drugs used in clinic 18 .…”
Section: Introductionmentioning
confidence: 99%
“…( 66 ) and Zastrozhin et al. ( 67 ) suggested that the miR-27 family, miR-142, miR-200a, miR-150 or miR-328 could targets to cyp3a4 ( 62 67 ). Therefore, our results extended the knowledge of miRNAs on cyp3a4 .…”
Section: Discussionmentioning
confidence: 99%
“…miRNA genes are an important class of fine-tuning regulators, playing a major role in a wide range of developmental, biological, and metabolic processes in plants, including metabolism, stress response, vegetative phase changes, organogenesis, and signal transduction ( Mathiyalagan et al, 2013 ). To date, a large number of miRNA families have been described in plants, some of which are directly associated with secondary metabolism synthesis ( Ekström et al, 2015 ). Increasingly, miRNAs have been identified and characterized in some important medicinal herbs ( Song et al, 2009 ; Wu et al, 2012b ) and different tissues of medicinal plants ( Xu et al, 2014 ; Khaldun et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%